CORTICAL BLINDNESS DUE TO BILATERAL STROKES - A CASE REPORT OF ANTON SYNDROME - Igor Mladenovski; Milan Mladenovski; Plamen Stoev; Stanislava Vasilkova; Maya Danovska (Peytchinski Publishing, 2023)
Background: Blindness (anopia) is a functional loss of vision, which could be due either to ophthalmological or neurological conditions. Blindness may be congenital or acquired. The main causes of blindness in adults are cataracts, uncorrected ametropia (myopia, astigmatism), glaucoma, macular dystrophy, cortical ischemic strokes, etc. In less than 10% of the patients, the reason for cortical blindness is bilateral occipital strokes, one of them hemorrhagic. Case Description: In the current case report, we present a 75-year-old patient with complaints of headache and visual loss. The patient has a history of a left PCA (posterior cerebral artery) distal ischemic stroke. The CT scan reveals a hypodense cerebral lesion in the left medial occipital cortex and subcortex (lingual gyri and cuneus) and a hyperdense cerebral lesion in the right medial occipital cortex and subcortex (lingual gyri and cuneus). The neurological examination shows only bilateral visual loss without motor deficits. The patient has visual anosognosia and confabulation in the setting of obvious visual loss and cortical blindness(Anton-Babinski syndrome, also known as ABS or Anton syndrome). However, performing cerebellar tests (dysdiadochokinesis, finger-to-nose test, heel-to-shin test, cerebellar ataxia) was not done because of the visual loss. After being consulted by a neurologist and neurosurgeon with the preliminary diagnosis of brain hemorrhage, the patient was admitted to the Neurology Clinic of UMHAT D-r "Georgi Stranski", Pleven, Bulgaria. Conclusion: Occipital infarction must be considered in all cases with sudden onset of isolated visual loss. Early diagnosis and treatment of stroke reduce mortality and morbidity. The prognosis depends on the extension of the visual cortex damage.